Clinical and Neurobiological Aspects of TAO Kinase Family in Neurodevelopmental Disorders - Hu, Chun; Feng, Pan; Yang, Qian; Xiao, Lin (Frontiers in Molecular Neuroscience, 2021)
Most of neurodevelopmental disorders (NDDs) share genetic risk factors. Recently, accumulating evidences imply the relevance of alterations in Tao kinases as a major determinant in several NDDs. Although it is well-known that Tao kinases are a highly conserved family of STE20 kinase and play important roles in multiple biological processes, the emerging roles of Tao kinases in neurodevelopment and NDDs remain to be intensively discussed. In this review, we summarize the potential roles of the Tao kinases based on structural and biochemical analysis, present the genetic data from clinic investigation and assessed the mechanistic link between the mutations of Tao kinases, neuropathology and behavioral impairment in NDDs.